The course of pain and dysphagia after radiofrequency ablation for Barrett’s esophagus-related neoplasia - Overwater, Anouk; Elias, Sjoerd G.; Schoon, Erik J.; Bergman, Jacques J. G. H. M.; Pouw, Roos E.; Weusten, Bas L. A. M. (Endoscopy, 2022)
Background Radiofrequency ablation (RFA) is effective for eradication of Barrett’s esophagus (BE) neoplasia, but little is known on the course of pain and dysphagia after RFA. We aimed to describe the course of post-RFA symptoms and to identify possible associated risk factors.Methods In this multicenter, observational cohort study, all RFA procedures registered in a prospective database were included. Patient and treatment characteristics were collected from medical records and patients self-registered post-procedural symptoms in electronic symptom diaries for 14 days. Mixed model regression was used for the analyses.Results In total, 255 diaries were completed. Post-RFA pain was reported for 95 % (95 %CI 93–98) of procedures (median duration 14 days; 25th–75th percentiles [p25–p75] 11–14) and major pain for 64 % (95 %CI 58–69; median duration 8 days, p25–p75 3–13). Post-procedural pain significantly increased with BE length, younger age, and no prior ablation. Dysphagia was present after 83 % (95 %CI 79–88) of procedures (median duration 13 days, p25–p75 9–14). The risk of dysphagia decreased with age and increased when patients experienced more pain.Conclusions RFA treatment for BE-related neoplasia seems a significant burden for patients, and post-procedural symptoms should be taken into account when counseling patients before starting endoscopic eradication therapy.